Fractures of carpal bones other than scaphoid – a narrative review - Andrzej Żyluk (Chirurgia Narządów Ruchu i Ortopedia Polska)
Fractures of the carpal bones are less common than fractures of the metacarpals and phalanges. The triquetrum and scaphoid are the most commonly affected bones, while injuries to other bones are less prevalent. The study aimed to provide updated information on carpal bone fractures other than the scaphoid, focusing on the incidence, fracture mechanism and pattern, diagnosis, methods, and treatment results. Each wrist bone fracture was thoroughly discussed in relation to these aspects. Additionally, the study presented the results of a literature review conducted in PubMed and Medline databases. In conclusion, fractures of the carpal bones other than the scaphoid are moderately common, with conservative treatment being the primary approach. Both conservative and surgical treatments yield good results.